Efeitos nutracêuticos do leite enriquecido com ômega 9, 6 e 3 em ratos submetidos à queimadura térmica por condução direta - Campelo, Ana Paula Bomfim Soares (2018)
In the present study mixtures of oils were used in nutraceutical concentrations with low ratio omega-9 : omega-3 with antioxidant properties, and low ratio omega-6 : omega-3 with anti-inflammatory properties. The aim of this study was to examine the effects of milk enriched with ω9, ω6 and ω3 (modified milk) oils in thermal burn. Forty-eight wistar rats, divided into four groups and followed two times (3 days and 21 days). The groups were as follows: Water, burned water (B+W), burned + milk (B+M), burned + modified milk (B+MM) with twelve animals in each group. Water, milk, and modified milk were administered for twenty-one consecutive days, ad libitum, to the respective groups after induction of burn on the animal's back which was performed with a 1 x 1 cm metal block heated electronically at 392 ºF. The evolution of body mass, fluid intake, feed intake, burned area involution, reepitheilalized epidermis thickness, collagen type, NFk-B expression, oxidative stress (MDA), reduced glutathione (GSH), activity of the glutathione peroxidase (GPx) and catalase were evaluated. On the third and the twenty-first day (D3 and D21), the animals were anesthetized, photographs of the lesions, then skin samples were collected for analysis. The B+MM group had a lower macroscopic lesion, a lower epidermal thickness and a higher proportion of collagen type I/III than the other burned ones. The MDA, GSH concentration of the B+MM group were the same as the Water group. The B+W and B+M groups had higher concentrations of MDA than the Water group. The GSH concentration of the B+MM group was higher than the B+A and B+M groups. The activity of the GPx and catalase enzymes, at different times, were higher in the B+MM group of the B+W and B+M groups. The mixes of omega-9, 6 and 3 oils decreases healing time with better collagen formation, inhibits NFkB expression and reduces oxidative stress.